Understanding the Value of Community Cloud : An exploratory multiple case study - Veenhuis, Lianne (My University, 2021)
The number of business interested in Cloud Computing is increasing, but many organisations are hesitant to use cloud-based IT services. Many difficulties are related to security and compliance. Community Cloud is a strategy for dealing with these issues, decreasing security and compliance issues, and achieving additional benefits like cost reduction and faster time to market. Community Cloud is a Cloud deployment model where the computational resources and infrastructure are exclusive to two or more organisations. Community Cloud has proven to be beneficial in some instances; however, research about the benefits and benefit drivers of Community Cloud is inadequate. The study aims to develop a model to evaluate the benefits of Community Cloud and illustrate the usage of the model by assessing the benefits of three Community Cloud cases. The obtained information from using the evaluation model can be used in the decision process of adopting a Cloud deployment model. Organisations can deploy a Community Cloud to improve their current operations and develop and extend their offerings. Based on the nature of the topic, the paper adopted an exploratory research strategy, including a multiple case study. Expert opinions, stakeholder interviews and literature review resulted in triangulated analysis of the subject. The contributions of the paper are twofold. First, the research shows a TOE-based benefits evaluation model for Community Cloud and second, it illustrates the use of the evaluation model reporting benefits in three Community Cloud cases.
Keywords: Community Cloud, Cloud Computing, Business Benefits, TOE framework, Benefit Evaluation Model, Digital Ecosystems